Innovative screen-printed electrodes on cork composite substrates applied to sulfadiazine electrochemical sensing - Tavares, Ana Patricia Moreira (2022)
This work reports the first use of cork as substrate to produce 3-electrode electrochemical devices, which may be very important to conduct sustainable worldwide biochemical testing in point-of-care. It consists of laminated cork covered by a thin-film of an insulating resin and printed in a 3-electrode system format. Silver ink was used to print electrical tracks and the reference electrode, while carbon ink was used to print working and auxiliary electrodes. The analytical performance of the cork-based devices was and compared to other common supports, as PET and ceramics in the form of screen-printed electrodes (SPEs). The cork-based devices displayed higher current values and better reversibility features and were able to undergo stable modification with conductive nanomaterials. They were further applied to detect sulfadiazine (SDZ), an antibiotic of human use that is also an environmental contaminant, by modifying the working electrode with a molecularly imprinted polymer (MIP) layer obtained by electropolymerization of pyrrol. The results confirmed the ability of the MIP film to detect SDZ selectively and showed reproducible increasing current signals for increasing concentrations of SDZ, from 8.0 to 186.0 μM. Direct comparison with commercial carbon SPEs showed greater sensitivity for the cork-based SPEs, with 10× lower limits of detection. Overall, cork-based devices are a valuable alternative to currently available SPEs systems, considering environment and cost features and also the analytical gains of this approach. These are especially important in times where a global biochemical testing became necessary for improved public health management.